Strategi Penggunaan Bahasa pada Berita "Pojok Kampung JTV" - Birda Ersalina Arofahtusholihah (ROLLING, 2020)
Pojok Kampung News Program is a news program that is produced and broadcast live on JTV television stations using Javanese language suroboyoan. Since it was first aired in 2001, the program has become a spectacle that is quite well known in the community. In fact, with shows that presented the news that took place in East Java, until now the Village Corner news program still exists in the community. The existence of the Corner Kampung news program, influenced by good production management and the application of ideas applied by the editors. The results of the strategies implemented by the editor, are obtained through rating and share values, thus influencing the existence of the program. The purpose of this study was to determine the actions and strategies applied by the editor in maintaining the existence of the Pojok Kampung news program. The results of the study indicate that the editorial of the Corner Kampung news program has followed the Standard Operating Procedure (SOP) well and structured. In addition, the application of 4 of the 13 elements of creative strategy was used by producers in maintaining the existence of the Kampung Corner news program.